Leave no scone unturned - Swanson, Denise (Swanson, Denise. Chef-to-go mystery., 2019)
It's the beginning of the university's fall semester and Dani can't wait for the college students to return to Normalton, Illinois<U+2015>after all, without them, there is no one to support her Lunch-to-Go service, which is a vital part of her Chef-to-Go business. But Normalton University's orientation week is marred by a mysterious murder, along with a series of car-jackings and sightings of a mysterious creature in a pond on campus. And with the whole town feeling unsettled, Dani finds herself dealing once again with the infuriatingly handsome Spencer Drake, the head of security at the university. Although Dani vowed that her life would never again be boring and routine after she quit her stifling corporate job, she had no idea that she'd end up dealing with such strange happenings<U+2015>not to mention murder. But as the trouble in Normalton draw worryingly close to home, Dani realizes that if the killer isn't caught soon, she may be the next one who is found scone cold dead.